Gambaran Strategi Coping Pasca Pacaran pada Mahasiswa yang MengalamiKekerasan Seksual - Yola Vanesa; Resha Yuwanda (Jurnal Riset Psikologi, 2024)
Currently, sexual violence against girlfriends often occurs. Sexual violence not only has an impact during dating, but also has long-term impacts after dating. This research aims to determine post-dating coping strategies for students who have experienced sexual violence while dating. This research focuses on post-dating coping strategies. The research method used is qualitative with a phenomenological ap proach. Data collection in this research was by interviews. Research participants were determined using a purposive sampling method, namely determination based on criteria. The criteria for participants in this study were female students aged 18-25 years w ho had experienced sexual violence in a relationship. The research results revealed that both participants received sexual violence in the form of unwanted kisses. One participant also experienced physical violence while dating. The second participant used Emotion Focused Coping as a coping strategy when dating, namely by apologizing to his girlfriend and crying. Meanwhile, after dating, the second participant used problem focus coping as a coping strategy, namely being more careful with the people he approached, watching films, telling stories to friends, and consulting a psychologist.